SOSIALISASI TEKNOLOGI TEPAT GUNA DALAM PRODUKSI GULA AREN DI DESA KALIABU, MAGELANG - Kusuma, Heri Septya; Bambang Sugiarto; Didi Saidi; Retno Dwi Nyamiati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Palm sugar has wide scope as an alternative sweetener in the Indonesian market. Palm sugar is a natural alternative to cane sugar which is less healthy and also more beneficial for farmers. The taste, sensory profile, and nutritional content of palm sugar vary based on the species, growing region, and climatic conditions. Currently, the traditional processing of palm sap in Kaliabu village results in lower yields and higher costs. There is enormous potential in the field of developing processing techniques (traditional processing, spray drying, membrane technology, and vacuum drying) to optimize palm sugar production in Kaliabu village. Spray drying is a non-conventional method that has the potential to be implemented in palm sugar production in Kaliabu village. This is because spray drying is quite good in terms of increasing antioxidant and phenolic content as well as storage capacity.